Cerebral perfusion and metabolism with mean arterial pressure 90 vs. 60 mmHg in a porcine post cardiac arrest model with and without targeted temperature management. (October 2021) - Skåre, Christiane; Karlsen, Hilde; Strand-Amundsen, Runar J.; Eriksen, Morten; Skulberg, Vidar M.; Sunde, Kjetil; Tønnessen, Tor Inge; Olasveengen, Theresa M.
Highlights: The optimal target for mean arterial pressure (MAP) after cardiac arrest is unknown. Animal models are useful for exploring how cerebral perfusion and metabolism varies with different blood pressure and temperature targets. In this cardiac arrest model, pigs randomised to targeting MAP to 90 mmHg had higher cerebral perfusion and flow, and more intact autoregulation compared to animals targeting MAP 60 mmHg, regardless of temperature management, however, without affecting ischaemic markers. Abstract: Aim: To determine whether targeting a mean arterial pressure of 90 mmHg (MAP90) would yield improved cerebral blood flow and less ischaemia compared to MAP 60 mmHg (MAP60) with and without targeted temperature management at 33 °C (TTM33) in a porcine post-cardiac arrest model. Methods: After 10 min of cardiac arrest, 41 swine of either sex were resuscitated until return of spontaneous circulation (ROSC). They were randomised to TTM33 or no-TTM, and MAP60 or MAP90; yielding four groups. Temperatures were managed with intravasal cooling and blood pressure targets with noradrenaline, vasopressin and nitroprusside, as appropriate. After 30 min of stabilisation, animals were observed for two hours. Cerebral perfusion pressure (CPP), cerebral blood flow (CBF), pressure reactivity index (PRx), brain tissue pCO2 (PbtCO2 ) and tissue intermediary metabolites were measured continuously and compared using mixed models. Results: Animals randomised to MAP90 had higher CPP (p < 0.001 for both no-TTM and TTM33) and CBF (no-TTM, p < 0.03; TH, p < 0.001) compared to MAP60 during the 150 min observational period post-ROSC. We also observed higher lactate and pyruvate in MAP60 irrespective of temperature, but no significant differences in PbtCO2 and lactate/pyruvate-ratio. We found lower PRx (indicating more intact autoregulation) in MAP90 vs. MAP60 (no-TTM, p = 0.04; TTM33, p = 0.03). Conclusion: In this porcine cardiac arrest model, targeting MAP90 led to better cerebral perfusion and more intact autoregulation, but without clear differences in ischaemic markers, compared to MAP60. Institutional protocol number: FOTS, id 8442.